2022
DOI: 10.3390/genes13020165
|View full text |Cite
|
Sign up to set email alerts
|

Splicing Variants, Protein-Protein Interactions, and Drug Targeting in Hutchinson-Gilford Progeria Syndrome and Small Cell Lung Cancer

Abstract: Alternative splicing (AS) is a biological operation that enables a messenger RNA to encode protein variants (isoforms) that give one gene several functions or properties. This process provides one of the major sources of use for understanding the proteomic diversity of multicellular organisms. In combination with post-translational modifications, it contributes to generating a variety of protein–protein interactions (PPIs) that are essential to cellular homeostasis or proteostasis. However, cells exposed to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 92 publications
(125 reference statements)
0
4
0
Order By: Relevance
“… 12 In fact, in lung cancer, the deregulation of isoforms of splicing regulators exists in common. 13 Some of the alternative splicing factors have been reported in the regulation of lung cancer. Min Chen et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 In fact, in lung cancer, the deregulation of isoforms of splicing regulators exists in common. 13 Some of the alternative splicing factors have been reported in the regulation of lung cancer. Min Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…12 In fact, in lung cancer, the deregulation of isoforms of splicing regulators exists in common. 13 Some of the alternative splicing factors have been reported in the regulation of lung cancer. Min Chen et al found 10 key alternative splicing factors in lung squamous cell carcinoma (LUSC) through bivariate cox regression analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting review analyzing the implication of alternative splicing in cancer is the one by Kim et al However, this review focuses on Hutchinson–Gilford progeria syndrome and small-cell lung cancer. The authors summarize how the formation of a neomorphic protein complex by protein isoforms encoded by distinct splice variants contribute to the pathogenesis of these diseases and suggest therapeutic strategies directed against these protein isoforms [ 13 ]. In malignant states, several cellular processes and mechanisms are deregulated, including autophagy.…”
mentioning
confidence: 99%